Competitividade dos biocombustíveis no Brasil: uma comparação entre os principais biocombustíveis etanol e biodisel - Ferrés, Diego Henrique Souza (2010)
Worldwide concerns about global warming and the harmful effects of fossil fuel use have encouraged the search for new energy models, based on clean and renewable sources, especially biofuels. No less important, the depletion of world reserves of fossil raw materials, coupled with geopolitical instability in key producing regions, boost, increasingly, the development of these new models. In this scenario, Brazil has an important role. World leader in the production and consumption of sugar cane ethanol, the country began in 2005 adding another source of renewable energy in its energy matrix: the blend of biodiesel in mineral diesel. This study aims to examine the competitiveness of the main Brazilian biofuels: ethanol and biodiesel. Firstly, these products were analyzed on its core features. Secondly, the economic competitiveness of these biofuels were compared to its direct substitutes derived from oil. Finally, the benefits (tangible and intangible) relating to the use of biofuels were analyzed, as well as how these intangible benefits should be priced, as a way to assign a prize to the positive benefits they bring to the environment and society. This thesis attempts to provide a basis for a further evaluation of the real economic competitiveness of biofuels compared to the petroleum fuels, as well as to put in check the main current analysis and criticism about the use of these products. Furthermore, this study aims to evaluate the potential and limitations of biofuel production in Brazil.